ISOLAT AKTIVITAS KITINOLITIK KAPANG DAN BAKTERI ENTOMOPATOGENIK SERTA POTENSINYA SEBAGAI PENGENDALI WERENG COKLAT (Nilaparvata lugen Stal) - , FATIMATUZ ZUHRO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
An isolation and examination of chitinolytic activity and mortality level of entomopathogenic fungi and bacteria from Brown planthopper were conducted in Laboratory of Ecology and Microbial Phisiology, LIPI-Cibinong. The aims of this study was obtained fungi and bacterial isolates that capable to control brown planthopper population effectively. Fourteen fungal (BW.1-BW.7 dan S.WR.F1- S.WR.F2) and seven bacterial isolates (S.WR.B1-S.WR.B7) were selected according to qualitative method based on halo-zone forming to calculate Index of Chitinolytic (IC). Quantitative assay of Chitinolityc activity by applying DNS (Dinitrosalicilyc acid) methode to measure NAG reducing sugar products of chitin degradation by extracellular chitinase secreted from isolates with higher level of IC. Mortality presentage of brown planthopper were calculated by bioassay running based on selected isolates direct application in liquid formulation contain 3 x 104 concentrations of bacterial cell or fungal conidia. The result showed that almost of bacterial isolates (accept S.WR.B4) were capable to form the halo-zone, where three high IC values belong to S.WR.B2, S.WR.B3 and S.WR.B6 0.518, 0.364 and 0.440 respectively. Only two fungal isolates designated BW.3 and BW.6 that showed halo-zone forming, with each number 0.53 and 0.38. The highest quantitative chitinolytic activity were S.WR.B2 and BW.3 with each value 0.0016 U/ml and 0.0014 U/ml. Both of them were also reach 30% and 23,3% of mortality presentage. Taken together, S.WR.B2 and BW.3 were the best bacterial and fungal isolate between another.